Meso-Rex bypass shunt vs. transposition shunt for cavernous transformation of portal vein in children - Lv, Yong; Pu, Lihui; Song, Jiulin; Yang, Jian; Zou, Guoyou; Yang, Jiayin; Xiang, Bo; Jin, Shuguang (Frontiers in Pediatrics, 2022)
Abstract Background: Cavernous transformation of portal vein (CTPV) causes portal hypertension in children. Among Meso-Rex treatments, it is unclear whether the Meso-Rex bypass shunt (MRB) or Meso-Rex transposition shunt (MRT) offers lower post-operative morbidity. Our objective was to evaluate post-operative outcomes comparing MRB and MRT for children with CTPV. Methods: A retrospective study was conducted of children undergoing Meso-Rex for CTPV from January 2010 to December 2020. The primary outcome was shunt complications including shunt stenosis and thrombus. The secondary outcome was re-operation. Results: Of 43 patients included, 21 underwent MRT and 22 underwent MRB. MRT were associated with a higher rate of shunt complications when compared to MRB (23.8% vs 9.1%, P = 0.191). Patients exhibited a higher rate of re-operation under the MRT than under the MRB (19% vs 4.5%, P = 0.138). The operative time in the MRT group was significantly shorter than in the MRB group. Compared to MRT, the reduction in the length and thickness of spleen were significantly greater in the MRB group. The increases in platelets was significantly higher in the MRB group than in the MRT group. The post-operative shunt velocity of MRB was notably faster than MRT. There was no significant difference in postoperative portal pressure among the two groups (P >0.05). Conclusion: Both MRB and MRT result in acceptable post-operative outcomes, but MRT is associated with higher post-shunt complications, often increase re-operation rate. This study suggests that MRB may offer advantages for children with CTPV.